2014
DOI: 10.1039/c4ra09520k
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, gradient extraction and surface polarity-dependent photoluminescence of cow milk-derived carbon dots

Abstract: Cow milk-derived carbon dots (CMCD) were separated using a simple and cheap "gradient extraction" method, which was applied for the first time in nanomaterials' separation. The surface polarity of the extracted CMCD correlates well with the polarity of the extraction solvent. Interestingly, the surface polarity also affects the photoluminescence (PL) of CMCD: a red-shift of PL was observed as the surface polarity increased, which was attributed to the increasing amount of polar functional groups on the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 35 publications
(31 reference statements)
1
36
0
Order By: Relevance
“…Realizing the need for cheap, renewable, abundant and ecofriendly carbon sources for the synthesis of biomoleculederived QDs (including C-QDs and G-QDs), biomass and their wastes have recently received great attention, and thus far served well to full the requirements for their synthesis. In this regard, various biomass and their wastes, for example, (i) agricultural products, [100][101][102][103][104][105][106][107] (ii) animals and their derivatives, [108][109][110][111][112] (iii) foods (including bakery products and beverages), [113][114][115][116][117][118][119] and (iv) industrial products, 120,121 have been demonstrated to be applicable for the scalable, low-cost synthesis of carbon-based QDs, with superior optical features and applications mostly in biological and sensing purposes. Agricultural products and their wastes, such as rice husk, sugar cane molasses and bagasse, chia seeds, coffee grounds, grass, dead neem leaves, and wood charcoal, have been used as carbon precursors for the fabrication of application-specic C-QDs and G-QDs.…”
Section: Qds From Biomass and Their Wastementioning
confidence: 99%
“…Realizing the need for cheap, renewable, abundant and ecofriendly carbon sources for the synthesis of biomoleculederived QDs (including C-QDs and G-QDs), biomass and their wastes have recently received great attention, and thus far served well to full the requirements for their synthesis. In this regard, various biomass and their wastes, for example, (i) agricultural products, [100][101][102][103][104][105][106][107] (ii) animals and their derivatives, [108][109][110][111][112] (iii) foods (including bakery products and beverages), [113][114][115][116][117][118][119] and (iv) industrial products, 120,121 have been demonstrated to be applicable for the scalable, low-cost synthesis of carbon-based QDs, with superior optical features and applications mostly in biological and sensing purposes. Agricultural products and their wastes, such as rice husk, sugar cane molasses and bagasse, chia seeds, coffee grounds, grass, dead neem leaves, and wood charcoal, have been used as carbon precursors for the fabrication of application-specic C-QDs and G-QDs.…”
Section: Qds From Biomass and Their Wastementioning
confidence: 99%
“…The highest quantum yield (QY) of the as‐prepared CDs was 21.7 %, which was higher than reported CDs obtained from other biomass materials . The high quantum yield could be resulted from the high level of nitrogen‐doping, which could greatly enhance the fluorescence intensity.…”
Section: Characterizationmentioning
confidence: 99%
“…Typically, organic solvents (e.g., ethyl acetate, acetone, chloroform, toluene, and n-hexane) are used to extract the amphiphilic C-dots and eliminate unreacted reagents in aqueous solution [111][112][113]. Recently, Han et al [99] proposed a novel "gradient extraction" method to separate C-dots synthesized from hydrothermal treatment of cow milk based on their surface polarity of the C-dots species (Figure 19). Four organic solvents with different polarities: hexane (polarity: 0.06), carbon tetrachloride (polarity: 1.6), mixture of carbon tetrachloride and dichloromethane (v/v = 3 : 2), and dichloromethane (polarity: 3.4), were used to extract C-dots fractions.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…For the characterization of Cdots, XPS has generally been used for the assessment of the elemental composition and the chemical bonds of C-dots in combination with IR. Doping of C-dots with nonmetallic heteroatoms such as N [43,49,56,99,114,121,122,134], S [14,24,46,49,87], Si [50,127,140,141], P [39,49,93], and B [114,142] has been characterized by XPS. A typical example of XPS analysis employed to estimate the surface states and chemical composition of nitrogen and sulfur-codoped C-dots (SNCNs) was displayed in Figure 6 [46].…”
Section: X-ray Photoelectronmentioning
confidence: 99%
See 1 more Smart Citation